Building playful resilience in higher education: Learning by doing and doing by playing - Heljakka Katriina (Frontiers Media SA, 2025)
Playful approaches include many benefits for higher education. Here, they denote elements of playful learning that invite students to engage with various challenges related to imagination, innovation, and co-creation. As stated in earlier research, playful learning follows the constructivism approach seeking students be active participants in their learning process, and tries to offer them surmountable challenges to learn while being intrinsically motivated-through learning by doing. Again, playful approaches include experimentation with uncertainty-through doing by playing. As particular instances of creative endeavors, they offer students joyful moments of discovery and possibilities to learn in a novel, but safe and failure-free situation and environment. This exploratory study presents new ideas on how playful learning methods, such as playful approaches may be used in higher education to contribute to the formation of playful resilience through playful activation. To substantiate this argument, we propose that playful learning approaches are similar to those used in the context of entrepreneurial education that aim to support the growth of a flexible, entrepreneurial mindset among students. Our suggestions for using playful approaches in higher education focus particularly on how a combination of playful tactics, tools, and tasks allow students to ideate, innovate, and create solutions to novel challenges. The contribution of the study is in linking the previously unconnected areas of higher education, playful approaches, playful resilience, and entrepreneurialism achieved through learning by doing, and doing by playing.